Strategic consensus on organizational performance: A contingency approach of organizational culture and isomorphic pressure - Muafi; Rizqi Adhyka Kusumawati (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: This research aims to test and analyze the consensus of organizational strategy with the contingency of organizational culture and isomorphism pressure which have an impact on organizational performance moderated by human capital. The survey is conducted to the owners/managers of Batik Micro Small Medium Entreprises (MSMEs) in 18 villages in Pekalongan, Indonesia. Design/methodology/approach: The data collecting is using questionnaire and interview to some owner/managers and leader of the Batik group. Pekalongan is a city of Batik that has Batik MSMEs spread in every area of the villages. Therefore, the sampling technique used in this research includes two stages: proportional area random sampling and purposive sampling. 17 MSMEs were taken as samples in each village. Furthermore, after selecting 17 MSMEs, the study used purposive sampling technique with a sample size of 170 MSMEs. This research uses three variables: isomorphism, organizational culture, and organizational strategy measured by semantic scale and use two bipolar typologies. As for organizational performance, it is measured using Likert scale. The data analysis technique is using Euclidience Distance Simple Regression with contingency approach and moderation of Euclidience Distance Simple Regression. Findings: These results provide are; (1) The higher the alignment degree between imitation strategy and hierarchy culture, the higher the organizational performance will be; (2) The higher the alignment degree between innovation strategy and adhocracy culture, the higher the organizational performance will be; (3) Human capital strengthens the consensus of imitation strategy with the contingency of hierarchy culture and benign isomorphism, so that the organizational performance is higher; (4) Human capital does not strengthen the consensus of innovation strategy with the contingency of adhocracy culture and hostile isomorphism, so that the organizational performance is higher. Research limitations/implications: The sampling technique of this research is done using purposive sampling, so it is feared that it cannot generalize to the existing population. The data collection also uses primary data with measurement approach based on the owner/manager perceptions, which sometimes still requires assistance and good understanding for the respondents. Organizational performance will be increase if the condition of hierarchy culture, benign isomorphism, and imitation strategy are supported by the moderation role of human capital that can strengthen the relationship with organizational performance. Practical implications: The higher the alignment degree between imitation strategy and hierarchy culture, the higher the organizational performance will be. If the organization tend to choose imitation strategy, it is more emphasizes on low market pressure, support from government regulation, low public and media pressure, and stable politic and safety, and vice versa. Originality/value: This research wants to fill the research gap by examining the importance of having an alignment of organization strategy (Imitation vs Innovation) related with the contingency of organizational culture (Hierarchy vs Adhocracy) and isomorphism pressure (Benign vs Hostile) so that Batik MSMEs entrepreneurs can further improve their organizational performance (operational performance and environmental performance).
Keywords: 650; organizational culture; isomorphism; organizational performance (operational performance and environmental performance); human capital